2020
DOI: 10.1186/s13058-020-01341-3
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype analysis of the internationally distributed BRCA1 c.3331_3334delCAAG founder mutation reveals a common ancestral origin in Iberia

Abstract: Background The BRCA1 c.3331_3334delCAAG founder mutation has been reported in hereditary breast and ovarian cancer families from multiple Hispanic groups. We aimed to evaluate BRCA1 c.3331_3334delCAAG haplotype diversity in cases of European, African, and Latin American ancestry. Methods BC mutation carrier cases from Colombia (n = 32), Spain (n = 13), Portugal (n = 2), Chile (n = 10), Africa (n = 1), and Brazil (n = 2) were genotyped with the genome-wide single nucleotide polymorphism (SNP) arrays to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
7
0
2
Order By: Relevance
“…These findings may contribute to genetic screening test strategies, support efforts to understand uncertain clinically significant variants, and involve laboratories, clinicians, patients, and relatives [27]. The European origin of the mutation was introduced early in the country's colonization, resulting in a high mutation prevalence in the population, mainly in the department of Huila (Southern Colombia) [28]. In our study cohort, 105 BRCA1/2 P/LP mutation carriers were identified.…”
Section: Discussionmentioning
confidence: 73%
“…These findings may contribute to genetic screening test strategies, support efforts to understand uncertain clinically significant variants, and involve laboratories, clinicians, patients, and relatives [27]. The European origin of the mutation was introduced early in the country's colonization, resulting in a high mutation prevalence in the population, mainly in the department of Huila (Southern Colombia) [28]. In our study cohort, 105 BRCA1/2 P/LP mutation carriers were identified.…”
Section: Discussionmentioning
confidence: 73%
“…The most prevalent one was c.3331_3334del, corresponding to 38.7% of the BRCA1 P/LP variants. This frameshift alteration was previously described as the second most commonly identified pathogenic BRCA1 variant in Brazil ( 13 ), was originated in Iberia and was later introduced to Colombia and South America at the time of Spanish colonization ( 24 ). The second most prevalent BRCA1 P/LP variant described in this cohort was c.5074+2T>C, corresponding to 25.8% of the cases.…”
Section: Discussionmentioning
confidence: 95%
“…Represented in different populations, it was first described in Canadian families [ 52 ]. To know the origin of this mutation, a study conducted in 2020 by Tuazon and collaborators [ 53 ] performed haplotype analysis with populations from Colombia, Spain, Portugal, Chile, Africa and Brazil and suggested that this mutation had a single origin in the Iberian Peninsula and was introduced in Colombia and South America at the time of Spanish colonization. This mutation was responsible for 10.2% of BRCA1 mutations found in Brazil in this review.…”
Section: Discussionmentioning
confidence: 99%